The impact of major league baseball on the incidence of operative hand and facial trauma at a level 1 trauma center - Ricci, Joseph A. (Arch Plast Surg, 2019)
BACKGROUND: Professional affiliation between medical centers and professional sports teams can be mutually beneficial in the provision of healthcare and marketing strategy. Anecdotal evidence suggests a link between trauma volume and sporting events; however, there is limited data. This study aims to characterize the incidence of operative hand and facial trauma during professional baseball home games. METHODS: A retrospective review of surgical cases for traumatic hand or facial injuries at a level 1 center between 1999 and 2012 was performed. Demographic information including date of injury, admission status, and operative repair were collected. Patients were grouped based on whether their trauma occurred on the date of a home game. RESULTS: Operative hand and facial trauma occurred at a rate of 33.4 injuries per 100 days with home games, compared to 22.2 injuries per 100 days (incidence rate ratios, 1.50; 95% confidence interval, 1.34–1.69). When home games were played, patients were more likely to present as a result of motorcycle accidents (3.1% vs. 1.5%; P=0.04) or bicycle accidents (5.0% vs. 2.6%; P=0.01). Other mechanisms of trauma were not statistically different. There was an increase incidence of injuries during home games in August; weekly variability showed an increased incidence during the weekends. CONCLUSIONS: There was an increased rate of operative hand and facial injuries on dates with professional home games. The incidence of injuries during home games was higher in the late summer and on the weekends. Further analysis may allow improved resource allocation and strategies for injury prevention and treatment.